2000
DOI: 10.1603/0022-2585-37.6.835
|View full text |Cite
|
Sign up to set email alerts
|

Vector Competence of Peruvian Mosquitoes (Diptera: Culicidae) for Epizootic and Enzootic Strains of Venezuelan Equine Encephalomyelitis Virus

Abstract: Mosquitoes collected in the Amazon Basin, near Iquitos, Peru, were evaluated for their susceptibility to epizootic (IAB and IC) and enzootic (ID and IE) strains of Venezuelan equine encephalomyelitis (VEE) virus. After feeding on hamsters with a viremia of approximately 10(8) plaque-forming units of virus per milliliter, Culex (Melanoconion) gnomatus Sallum, Huchings, & Ferreira, Culex (Melanoconion) vomerifer Komp, and Aedes fulvus (Wiedemann) were highly susceptible to infection with all four subtypes of VEE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 18 publications
1
60
0
6
Order By: Relevance
“…taeniopus to oral infection by epizootic subtype IAB VEEV is the result of a midgut infection/ escape barrier and not a salivary gland infection barrier. 3,17,20 In contrast, epizootic vectors do not appear to exhibit subtypespecific infection barriers to the same extent as enzootic vector mosquitoes. 8,10,20 T able 2 Infection, dissemination, and transmission proportions for Culex taeniopus mosquitoes infected with enzootic and equine-virulent Venezuelan equine encephalitis virus subtype IE* The proportions of infection for the 68U201 VEEV strain in Cx.…”
Section: Discussionmentioning
confidence: 99%
“…taeniopus to oral infection by epizootic subtype IAB VEEV is the result of a midgut infection/ escape barrier and not a salivary gland infection barrier. 3,17,20 In contrast, epizootic vectors do not appear to exhibit subtypespecific infection barriers to the same extent as enzootic vector mosquitoes. 8,10,20 T able 2 Infection, dissemination, and transmission proportions for Culex taeniopus mosquitoes infected with enzootic and equine-virulent Venezuelan equine encephalitis virus subtype IE* The proportions of infection for the 68U201 VEEV strain in Cx.…”
Section: Discussionmentioning
confidence: 99%
“…8,10 The CO-San Miguel forest exhibited higher mosquito diversity than any of the Catatumbo forests, but particularly it showed a richer fauna of Culex (Melanoconion) species ( That mixture of mosquitoes was also demonstrated to transmit VEE virus experimentally. 33 However, the titers of virus in the viremic hamsters used in those infection studies are far higher than those reported after experimental infection of natural reservoir hosts. 34,35 Our results suggest that the greater abundance, diversity, and constancy of suspected enzootic vectors (subgenus Melanoconion species) in CO-San Miguel site partly explain the regularity and higher rates of VEE virus isolations.…”
Section: Discussionmentioning
confidence: 92%
“…titillans seem to comply with the above criteria for all three forests. 33,[42][43][44][45][46] These species are also common in the forest and surrounding open areas in another enzootic foci of VEE virus in northern Venezuela. 36 Future studies should investigate the movement of VEE virus away from enzootic foci into open areas, and its interaction with equines and other potential amplifying hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Biomédica 2003;23 (Supl.1):125). Experimentalmente, en el área de Iquitos (Perú) se ha demostrado que es un vector competente del subtipo ID (30). Cx.…”
Section: Discussionunclassified